Microbial endocrinology: the microbiota-gut-brain axis in health and disease - Cryan, John F.; Lyte, Mark (Advances in Experimental Medicine and Biology, 2014)
The field of microbial endocrinology is expressly devoted to understanding the mechanisms by which the microbiota (bacteria within the microbiome) interact with the host ("us"). This interaction is a two-way street and the driving force that governs these interactions are the neuroendocrine products of both the host and the microbiota. Chapters include neuroendocrine hormone-induced changes in gene expression and microbial endocrinology and probiotics. This is the first in a series of books dedicated to understanding how bi-directional communication between host and bacteria represents the cutting edge of translational medical research, and hopefully identifies new ways to understand the mechanisms that determine health and disease.